Network traffic recovery from link-load measurements using tensor triple decomposition strategy for third-order traffic tensors - Ming, Zhenyu; Qin, Zhenzhi; Zhang, Liping; Xu, Yanwei; Qi, Liqun (Journal of computational and applied mathematics, 2024)
Network traffic data is the pivot of input in many network tasks but its direct measurement can be insufferably costly. In this paper, we propose a network traffic recovery method which only requires the conveniently measurable link-load traffics. We arrange the traffic data as a third-order tensor and utilize the triple decomposition technique proposed very recently by Qi et al. (2021). The studied model is a differentialble unconstrained minimization problem, which can be efficiently solved by a Barzilai–Borwein (BB) gradient algorithm. We prove that the generated iteration sequence can globally converge to a certain stationary point of the objective function. The numerical simulations on three open-source traffic datasets demonstrate the superiority of our method in comparison with other state-of-the-art algorithms.